Auditory stimulation with music influences the geometric indices of heart rate variability in response to the postural change maneuver - Castro, Bianca C. R. de [UNESP] (2014)
It is poor in the literature the behavior of the geometric indices of heart rate variability (HRV) during the musical auditory stimulation. The objective is to investigate the acute effects of classic musical auditory stimulation on the geometric indexes of HRV in women in response to the postural change maneuver (PCM). We evaluated 11 healthy women between 18 and 25 years old. We analyzed the following indices: Triangular index, Triangular interpolation of RR intervals and Poincar plot (standard deviation of the instantaneous variability of the beat-to beat heart rate [SD1], standard deviation of long-term continuous RR interval variability and Ratio between the short - and long-term variations of RR intervals [SD1/SD2] ratio). HRV was recorded at seated rest for 10 min. The women quickly stood up from a seated position in up to 3 s and remained standing still for 15 min. HRV was recorded at the following periods: Rest, 0-5 min, 5-10 min and 10-15 min during standing. In the second protocol, the subject was exposed to auditory musical stimulation (Pachelbel-Canon in D) for 10 min at seated position before standing position. Shapiro-Wilk to verify normality of data and ANOVA for repeated measures followed by the Bonferroni test for parametric variables and Friedmans followed by the Dunns posttest for non-parametric distributions. In the first protocol, all indices were reduced at 10-15 min after the volunteers stood up. In the protocol musical auditory stimulation, the SD1 index was reduced at 5-10 min after the volunteers stood up compared with the music period. The SD1/SD2 ratio was decreased at control and music period compared with 5-10 min after the volunteers stood up. Musical auditory stimulation attenuates the cardiac autonomic responses to the PCM.